La producción audiovisual en El Salvador - Tovar, Diego; Cárcamo, Diana A.; Coto, Gabriela M.; Gaitán, Angie. A.; Henríquez, Karla P. (Realidad Empresarial, 2017)
No hay resúmenes disponibles. Realidad Empresarial No. 3, 2017: 27-33